Service user interview panels for recruitment to UK child and adolescent mental health services: A questionnaire study exploring the experiences of young people, staff and candidates - Sophie Allan; Emma Travers-Hill (The Beryl Institute, 2019)
Service user involvement is increasingly important in health and social care policy, including in Child and Adolescent Mental Health Services (CAMHS), but evidence evaluating involvement initiatives is lacking. This questionnaire study evaluated the use of young people's (YP) interview panels in the recruitment of CAMHS staff, from the perspectives of YP, candidates and members of the staff interview panels. Self-report questionnaires were administered to YP, candidates and staff interview panel. This included quantitative and qualitative "free text" responses. YP's panels were found to be important in hearing the voices of YP; participants all stated they would like YP to take part in future interviews. Qualitative analysis found YP provided added insight into the process, had a professional manner, were valued and important, gave clear feedback, and benefitted the YP involved. A number of changes to the process were identified. This evaluation found YP's interview panels were feasible, and a valuable addition to the recruitment process, and should be considered in other CAMHS teams. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.